An Assessment of Association of Gravidity of Pregnant and Non-Pregnant Females with Periodontal Health and Periodontal Treatment Needs - Syeda Tahreem Fatima, Tasveeb Momin, Muhammad Anas Nasim, Fahmina Jamil, Hira Butt, Maria Jabbar, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To assess the association of gravidity of pregnant and non-pregnant females with their periodontal health and treatment needs. Methodology: A cross sectional study was conducted from March 2019 to August 2019 among 44 pregnant and 52 non-pregnant women visiting the gynecology department of Sharif Medical and Dental College and Raiwind Polyclinic, Lahore (community outreach program of the institute) using non-probability convenient sampling technique. Data was collected using the Community Periodontal Index of Treatment Needs (CPITN). Results: A non-significant association was seen between the periodontal health and gravidity of pregnant females (p=0.454) and non-pregnant females (p=0.863). Most of the primigravida had periodontal treatment needs (TN1). TN 2 was required by both groups equally Conclusion: Primigravida pregnant females had a higher percentage of healthy periodontium while the multigravida pregnant females had more calculus deposition and a higher percentage of pocket depth 4-5mm. The multigravida non-pregnant patients had calculus deposition as their major periodontal problem followed by bleeding gums. Most of the primigravida pregnant females required oral hygiene instructions and had periodontal treatment needs (TN1). Those requiring (TN 2) were approximately equal in both groups while none of the females from both the groups required complex treatment (TN3). Keywords: Primigravida, Multigravida, periodontal health, pregnant females, periodontal treatment needs.